Dyadic Coping in Couples Facing Chronic Physical Illness: A Systematic Review - Weitkamp, Katharina; Feger, Fabienne; Landolt, Selina A.; Roth, Michelle; Bodenmann, Guy (Frontiers in Psychology, 2021)
Objective: Chronic physical illness affects not only patients but also their partners. Dyadic coping (DC) – the ways couples cope in dealing with a stressor such as chronic illness – has received increased attention over the last three decades. The aim of the current study was to summarize the state of research on DC in couples with chronic physical illnesses. Methods: We conducted a systematic review of qualitative, quantitative, and mixed-methods studies published between 1990 and 2020, assessing DC in couples affected by severe physical illnesses. We used DC and related search terms for the literature search in Psycinfo, Psyndex, and Medline. 5,330 studies were identified in three electronic databases and 49 of these were included in the review (5,440 individuals reported on 2,820 dyads). We excluded studies on cancer, cardiovascular disease, and multiple sclerosis because of existing reviews in the respective fields. Half of the studies included were on diabetes. Other studies were on arthritis, chronic obstructive pulmonary disease, cystic fibrosis, human immunodeficiency virus (HIV), Huntington’s disease, lupus erythematosus, Parkinson’s disease, renal diseases, stroke, and endometriosis. Two raters extracted data using a predefined protocol, including study quality. Results were collated in a narrative synthesis organized by illness and DC operationalization. Results: Overall, DC was associated with beneficial outcomes in physical health, well-being, and relationship satisfaction. Differential effects became apparent for certain chronic conditions potentially depending on certain disease characteristics, such as early-onset, sudden-onset, or life-threatening conditions. Conclusion: Facing challenges together as a couple seemed indispensable for adapting to a diverse range of demands related to chronic illnesses with some specific demands of particular chronic diseases. There is a need for the development of truly dyadic interventions with an eye on the specific challenges of the various chronic conditions.